PERAN BPBD PROVINSI SUMATERA SELATAN DALAM MENINGKATKAN KINERJA SATUAN TUGAS (SATGAS) UNTUK MENANGGULANGI BENCANA KEBAKARAN HUTAN DAN LAHAN - Aryanisila, Aryanisila (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
The main focus of this study is the role of the Regional Disaster Management Agency (BPBD) of South Sumatera in improving the performance of the task force (Satgas) to overcome forest and land fire disasters. The purpose of this study is to observe the role of BPBD in improving the performance of the task force to overcome land and forest fire disasters, especially in South Sumatra Province. The research method used in this study is a qualitative method with data collection techniques through observation and in-depth interviews and data triangulation. Based on the findings in this study, it shows that the role of the Regional Disaster Management Agency (BPBD) in improving the performance of the task force to overcome forest and land fire disasters has been running well, but there are still several obstacles in efforts to prevent forest and land fires in South Sumatera, namely limited Human Resources (HR), limited facilities and infrastructure, lack of human awareness to protect the surrounding environment.